Micronucleus formation in human cancer cells is biased by chromosome size - Bochtler, Tilmann; Kartal-Kaess, Mutlu; Granzow, Martin; Herold-Mende, Christel; Jauch, Anna; Krämer, Alwin (Genes, chromosomes & cancer, 2019)
Chromosomal instability is one of the hallmarks of cancer and caused by chromosome missegregation during mitosis, a process frequently associated with micronucleus formation. Micronuclei are formed when chromosomes fail to join a daughter nucleus during cell division and are surrounded by their own nuclear membrane. Although it has been commonly assumed that the gain or loss of specific chromosomes is random during compromised cell division, recent data suggest that the size of chromosomes can impact on chromosome segregation fidelity. To test whether chromosome missegregation rates scale with chromosome size in primary human cancer cells, we assessed chromosome sequestration into micronuclei in patient-derived primary NCH149 glioblastoma cells, which display high-level numerical chromosome instability (CIN), pronounced spontaneous micronucleus formation but virtually no structural CIN. The cells were analyzed by interphase fluorescence in situ hybridization using chromosome-specific painting probes for all chromosomes. Overall, 33% of early passage NCH149 cells harbored micronuclei. Entrapment within a micronucleus clearly correlated with chromosome size with larger chromosomes being significantly more frequently missegregated into micronuclei than smaller chromosomes in primary glioblastoma cells. These findings extend the concept that chromosome size determines segregation fidelity by implying that size-specific micronucleus entrapment occurs in primary human cancer cells as well.